2021
DOI: 10.3390/molecules26102922
|View full text |Cite
|
Sign up to set email alerts
|

Women in the Singlet Fission World: Pearls in a Semi-Open Shell

Abstract: Singlet fission, a multiple exciton generation process, can revolutionize existing solar cell technologies. Offering the possibility to double photocurrent, the process has become a focal point for physicists, chemists, software developers, and engineers. The following review is dedicated to the female investigators, predominantly theorists, who have contributed to the field of singlet fission. We highlight their most significant advances in the subject, from deciphering the mechanism of the process to designi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 87 publications
(109 reference statements)
0
1
0
Order By: Relevance
“…For example, molecules with a moderate (0.5) diradical character, i.e., diradicaloids, possess unusually high values of the second hyperpolarizability and are attractive for application in organic photonics [9][10][11][12]. It was also shown that compounds with a low-to-intermediate (0.1-0.5) diradical character are potential singlet fission materials [13][14][15][16]. Singlet fission is a phenomenon in which one absorbed photon is converted into two excitons.…”
Section: Introductionmentioning
confidence: 99%
“…For example, molecules with a moderate (0.5) diradical character, i.e., diradicaloids, possess unusually high values of the second hyperpolarizability and are attractive for application in organic photonics [9][10][11][12]. It was also shown that compounds with a low-to-intermediate (0.1-0.5) diradical character are potential singlet fission materials [13][14][15][16]. Singlet fission is a phenomenon in which one absorbed photon is converted into two excitons.…”
Section: Introductionmentioning
confidence: 99%